Polimorfisme Protein Serum Darah Induk Sapi Beranak Kembar dan Tunggal pada Sapi Peranakan Ongole dan Keturunan Simental (BLOOD SERUM PROTEIN POLYMORPHISM OF THE COW DELIVERED TWIN OR SINGLE CALVES IN ONGOLE GRADE AND SIMENTAL CROSSBRED) - Yuwono, Tri; Sumeidiana, Irene; Ondho, Yon Soepri; Kurnianto, Edy (Jurnal Veteriner, 2017)
The twinning cow is presumable have difference in blood protein typology with the single cow. Thestudy investigated blood protein polymorphism in twinning and single of ongole grade and Simmentalcrossbred cows. The study used four twinning versus eight single ongole grade and seven twinning versussix single Simmental crossbred cows. Blood samples were analyzed by using marker ExactPro BroadRange (10-245kDa) and Sodium Dodecyl Sulphate-polyacrilamide Gel Electrophoresis method, to estimatethe loci of albumin (Alb), post-albumin (Pa), ceruloplasmin (Cp), transpherrin (Tf), and amylase-I (Amy-I).The genetic variation was analyzed based on the value of gene frequency, individual heterozigosity andaverage heterozigosity. In this study the twinning ongole grade cows had lower average heterozigosity(0.46) than the single ongole grade cows (0.49). The twinning Simmental crossbred cows had lower averageheterozigosity (0.35) than the single Simmental crossbred cows (0.40). The average heterozigosity ofongole grade cows had higher value than Simmental crossbred cows. The average heterozigosity rangedfrom 0.35-0.49, which was indicated high genetic variation in all cows. Higher gene frequency of allelealbumin A than albumin B influences the twinning trait in ongole grade and Simmental crossbred cows.
Keywords: cow; twin birth; polymorphism; genotype; heterozigosity